2014
DOI: 10.1123/ijsnem.2014-0033
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Training Adaptations in Aquatic Sports

Abstract: The adaptive response to training is determined by the combination of the intensity, volume, and frequency of the training. Various periodized approaches to training are used by aquatic sports athletes to achieve performance peaks. Nutritional support to optimize training adaptations should take periodization into consideration; that is, nutrition should also be periodized to optimally support training and facilitate adaptations. Moreover, other aspects of training (e.g., overload training, tapering and detrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 69 publications
(75 reference statements)
0
41
0
3
Order By: Relevance
“…Training strategies that adapt the muscle to maximize the contribution of fat to energy production during such swimming are encouraged (see Mujika et al, 2014). Nevertheless, in longer races, muscle carbohydrate stores may become limiting, and an exogenous supply of this fuel source is needed to sustain swimming speed.…”
Section: Energy Provision During Racing Carbohydrate For Open-water Pmentioning
confidence: 99%
“…Training strategies that adapt the muscle to maximize the contribution of fat to energy production during such swimming are encouraged (see Mujika et al, 2014). Nevertheless, in longer races, muscle carbohydrate stores may become limiting, and an exogenous supply of this fuel source is needed to sustain swimming speed.…”
Section: Energy Provision During Racing Carbohydrate For Open-water Pmentioning
confidence: 99%
“…Moreover, even though this study did not intend to report individual data, we observed that several athletes presented a chronic deficit in carbohydrate consumption throughout the season. Thus, although some studies suggest that carbohydrate restriction in specific situations can enhance adaptations to training 22 , carbohydrates are traditionally considered as the fundamental source to energy supply 23 and post-exercise recovery 1 . In other words, it is likely that a chronically low carbohydrate diet has negative effects on conditioning and sports performance.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the planning is performed so that athletes can reach their best physical fitness and technique in the most important competition in the season 1 . It is well established that nutrition plays a crucial role in sports performance 2 , since a proper diet providing the athlete's nutritional requirements helps to obtain morphological and physiological adaptations and optimizes performance in training and competitions 1,3,4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations